Characteristics of Wastewater Generated by the Snack Food (Cookies) Industry - Ahmad Habibi; Sjaifuddin Sjaifuddin; Juwarin Pancawati (Universitas Diponegoro, 2024)
The snack food industry is one of the major industries in Indonesia that has various types of products, one of which is snacks (cookies), which are widely consumed as snacks. This study aims to determine the characteristics of wastewater from the snack food industry (cookies). The research was conducted in three factories located in Bandung Regency, Sumedang Regency and Majalengka Regency. Primary data were collected from wastewater samples collected monthly for laboratory testing. Data analysis used descriptive statistical analysis of average concentration of wastewater parameters using Microsoft Excel software and SPSS 25 software. The main parameters of wastewater from the snack food industry (cookies) are pH, TSS, BOD, COD, ammonia, total nitrogen, and MBAS. From the comparison of the resulting BOD, COD, TSS, ammonia, and total nitrogen pollutant loads, the largest load trends occur in Factory B, Factory C, and Factory A. Failure to properly treat these crucial wastewater parameters can pose risks to the environment and surrounding communities. Thus, these vital parameters form the basis for selecting wastewater treatment plant technology to fulfil environmental standards. WWTP process recommendations that can be used are grease trap, surge tank, dissolved air flotation (DAF), anaerobic system, aerobic system, secondary clarifier, and post-treatment.